A note on the dosimetric interpretation of rigidity spectra for solar particle beams - Schaefer, Hermann J.; United States.; Naval Aerospace Medical Institute (U.S.) (U.S. Naval Aerospace Medical Institute, U.S. Naval Aviation Medical Center, 1966)
By using the experimental rigidity formulation as proposed by Freier and Webber, the particle fluxes of all flare events of the past solar cycle can be uniformly described in terms of a flux constant J sub o and a rigidity constant P sub o. On the basis of these data, three fictitious rigidity spectra are 'synthesized' covering the full variability range of all flare events, yet characterizing more systematically the relationships between the basic dosimetric quantities and the rigidity constant P sub o. It is found that, of the components heavier than protons, only alpha particles contribute substantially to total exposure. The fractional alpha dose in the tissue surface behind 0.1 g/sq cm shielding grows from 40 percent for P sub o = 50 Mv to 400 per cent for P sub o = 300 Mv. At the same time, the depth dose of the alpha component shows an extremely steep drop which would require microsensors for accurate measurement. For the alpha and medium heavy components, the RBE shows a pronounced transition in near surface regions which further steepens the drop of the RBE dose equivalents as compared to the rad doses. The extremely strong and nonlinear dependence of the rad and rem dose distribution on rigidity makes the rigidity concept practically useless for any dosimetric evaluation and indicates the need for direct measurements of local rad and rem doses on the astronaut's body. (Author).
"Bureau of Medicine and Surgery, MFO 22.03.02-5001.34, NASA Order No. R-75."--title page.
Joint report of the United States Naval Aerospace Medical Institute and the National Aeronautics and Space Administration.--cover.
"26 April 1966."
Includes bibliographical references (page 12)
By using the experimental rigidity formulation as proposed by Freier and Webber, the particle fluxes of all flare events of the past solar cycle can be uniformly described in terms of a flux constant J sub o and a rigidity constant P sub o. On the basis of these data, three fictitious rigidity spectra are 'synthesized' covering the full variability range of all flare events, yet characterizing more systematically the relationships between the basic dosimetric quantities and the rigidity constant P sub o. It is found that, of the components heavier than protons, only alpha particles contribute substantially to total exposure. The fractional alpha dose in the tissue surface behind 0.1 g/sq cm shielding grows from 40 percent for P sub o = 50 Mv to 400 per cent for P sub o = 300 Mv. At the same time, the depth dose of the alpha component shows an extremely steep drop which would require microsensors for accurate measurement. For the alpha and medium heavy components, the RBE shows a pronounced transition in near surface regions which further steepens the drop of the RBE dose equivalents as compared to the rad doses. The extremely strong and nonlinear dependence of the rad and rem dose distribution on rigidity makes the rigidity concept practically useless for any dosimetric evaluation and indicates the need for direct measurements of local rad and rem doses on the astronaut's body. (Author).
Keywords: Particle beams. / http://id.loc.gov/authorities/subjects/sh85098361; Solar flares. / http://id.loc.gov/authorities/subjects/sh85124511